A Biological and Ecological Study of Ruditapes decussatus (Bivalvia, Veneridae) in Lattakia City Coast - Ammar, Ezdihar; Darwich , Fayrouz; Tayar, Helen (Latakia University Journal -Biological Sciences Series, 2013)
This research aimed to study the growth and reproduction of Ruditapes decussatus, and determine the suitable conditions for its culture. The individuals were collected from the intertidal zone near the Higher Institute of Marine Research during September 2011 till June 2012 once a month. Samples of sea water were also collected to study phytoplankton which feed the Ruditapes decussatus, and its abundance. The laboratory study conducted included distinguishing between males and females of all individuals, conducting morphometric measurements of shells to determine wet and dry weight of the soft body, determining period of sexual maturity and condition index, and evaluating the growth condition through the index. GSI (gonad somatic index) mean values ​​ refer to the existence of two peaks referring to two reproduction periods: one in fall and another in spring. While the mean values ​​refer to adequate food and growth. The study also shows the possibility of acclimatization this species easily at laboratory conditions. The abundance values of phytoplankton ​​ranged between (2777.778 - 7291, 667 Cell/L) reaching its highest value during spring (7921, 667 Cel/L).